PENGARUH KOMPENSASI, BUDAYA ORGANISASI DAN GAYAKEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN - NOERDIANSYAH, AVIF (Jurnal Ilmu Manajemen (JIM), 2013)
Employees is one of the factors production that is notenough to be compensated only, but also through the adjustment ofthe company’s values and the support of their leaders can indirectlyincrease employee job satisfaction. The purpose of this research totest the influence of compensation, organizational culture is limited tothe hierarchy culture and leadership style on employees jobsatisfaction in PT. PLN (Persero) North Surabaya Area. Samplingtechnique in this research using proportionate stratified randomsampling with 56 samples of respondents, however, of the distributingquestionnaires to 56 respondents only 38 questionnaires arereturned. The results of research showed that compensation have asignificant positive influence on employee job satisfaction.Organizational culture have a significant positive influence onemployee job satisfaction. Leadership style had not significantinfluence on employee job satisfaction. Compensation, organizationalculture and leadership style have a significant simultant influence onemployee job satisfaction.Keywords: compensation, organization culture, leadership style, job satisfaction.